Adoption of Climate-Smart Agriculture Technologies in Tanzania - Kurgat, Barnabas K.; Lamanna, Christine; Kimaro, Anthony; Namoi, Nictor; Manda, Lucas; Rosenstock, Todd S. (Frontiers in Sustainable Food Systems, 2020)
Climate-smart agriculture (CSA) is agriculture that increases productivity, improves resilience, and mitigates climate change. Smallholder adoption of farming technology is necessary to speed the transition to CSA. Here, we assessed the determinants of adoption of five technologies that can help achieve some of the CSA outcomes in smallholder farms in Tanzania. They included: crop and livestock diversification, irrigation, application of chemical fertilizers, and agroforestry. Using data collected from 821 farming households, a multivariate probit model was employed to evaluate the determinants of adoption, allowing for examination of synergies and trade-offs between the technologies. Application of chemical fertilizers was fairly well adopted (34% of farmers), while irrigation was least adopted (26%). Some technologies, including crop diversification and irrigation, as well as application of chemical fertilizer and agro-forestry, complemented each other. Trade-offs were observed between livestock diversification and irrigation. Female control of farm resources, farm location, and household resources were major determinants of adoption. We therefore, recommend strategies that seeks to enhance building household resource as pathway for improved adoption of new technologies.